On-Demand Beam Scheduling Technology of Low-Orbit High-Throughput Satellite - Shuai HAN; Yihang WU; Jixi LI; Zuting CHEN; Siyue SUN; Guang LIANG (天地一体化信息网络)
Low-orbit high-throughput satellite internet can satisfy the increasing speed and connection density requirements of end users and provide users with all-weather low-latency ultra-broadband communication services.At the same time, how to adapt to the fl exible and unevenly distributed terrestrial service requirements in low-orbit downlink scenarios and improve system throughput is an urgent problem to be solved.Based on the modeling of the beamforming architecture of the low-orbit highthroughput satellite downlink system and the satellite-to-earth fading of the low-orbit satellite and the inter-beam interference of the high-throughput satellite, the low-orbit high-throughput satellite downlink channel model was established.Based on the research of the high-throughput satellite on-demand beam scheduling scheme, the beam scheduling optimization problem model was established to ensured the utilization of resources, and the on-demand beam scheduling technology for high-throughput satellite internet was proposed, the method of using a small amount of beams to cover multiple cells by using on-demand time division multiplexing improved the utilization rate of resources, effectively suppressed the interference between beams, and improved the throughput of the system.